A pilot study of the responsiveness of wireless motion analysis in facioscapulohumeral muscular dystrophy. Issue 5 (9th September 2019) - Statland, Jeffrey M.; Karanevich, Alex; Bruetsch, Adam; Huisinga, Jessie
Abstract: Introduction: We determined whether instrumenting timed functional tasks with wireless inertial motion sensors were responsive to facioscapulohumeral muscular dystrophy (FSHD) progression and movement pattern changes. Methods: Ten individuals who were clinically affected with genetically confirmed FSHD, mean age 54 years (range 42–65), performed an instrumented timed up and go (iTUG) trial at each visit, wearing six wireless inertial sensors. We determined the estimated average monthly slope of progression and 12‐month change for temporal and spatial motion variables using a linear mixed effects model. Results: For an average of 20.6 months (range 6.1–34.5), the iTUG duration stayed constant, whereas stride length, stride velocity, and trunk sagittal range of motion changed, indicating poorer performance. Arm swing changed in a compensatory direction toward the normative mean. Discussion: This study provides preliminary evidence that iTUG motion variables could be sensitive to progression in FSHD, but this requires validation in a larger study.